Implementasi Teknologi Tepat Guna Mesin Pemarut Jahe dan Expired Date Pada Proses Produksi Jahe Instan Sebagai Produk Unggulan Kabupaten Pemalang - Broto, Wisnu; Arifan, Fahmi; Supriyo, Edy; Kartikasari, Nanik; Prasetyo, Alif Nur Fauzi; Utami, Palupi Diah (Sekolah Vokasi Universitas Diponegoro, 2023)
Kelareyan Village, Pemalang Regency is topographically a lowland area which is also the economic traffic of Pemalang district, so it is very suitable for agricultural and trading businesses. Kelareyan Village trading commodities are people's daily commodities such as food, beverages, clothing, medicine, and so on. With the position of the region, Kelareyan Village has enormous economic potential from the agricultural and trade sectors. The potential in question is the existence of a herbal beverage production center. In Kelareyan Village, there is a Kelareyan Independent Farmer Business Group (KUT) owned by Mr. Eko by producing instant ginger drinks from ginger-based ingredients. The problem faced by the Independent Farmer Business Group (KUT) is the contraction for ginger grinding with simple manual tools, causing the size of fine ginger to be not uniform so that it is less optimal in quality and quantity of production and other problems, namely the expired date printer that is still simple (stampel) so that it can still be quickly lost on the packaging. Therefore, the community service program that will be implemented focuses on socialization innovations and training on the use of ginger shredding machines and automatic expired date machines. In addition, the program was made with the aim that the Kelareyan Independent Farmer Business Group (KUT) can be more optimal in producinginstant ginger drinks.